Pengembangan Media Pembelajaran Berbasis Web Pada Uji Kompetensi Skema Sertifikasi Teknisi Muda Jaringan Komputer - MANGGALA YULIANTA, KRESNA; ANISTYASARI, YENI (IT-Edu : Jurnal Information Technology and Education, 2019)
AbstractThis research was conducted to develop learning media applications to help competency test participants in learning the material to be tested. The formulation of the research problem is: (1) How to develop Web-Based Learning Media in the Competency Test of the Young Computer Network Technician Certification Scheme. (2) How is the quality of Web Based Learning Media in the Competency Test of the Young Computer Network Technician Certification Scheme. (3) What is the response of participants to Web-Based Learning Media in the Competency Test of the Computer Network Young Technician Certification Scheme. The research method used is the Waterfall method. The research objectives in this study were 20 students who were or had attended a computer network course. The results of the study show that: (1) Learning Media developed has a percentage of 86.76% of the assessment from the validator. This percentage is included in the very feasible category with a percentage range of 81% -100%. From these results, it can be concluded that the application of learning media strongly agrees to the trial of media validators. Keywords: Application, Learning Media, Website.Abstrak Penelitian ini dilaksanakan untuk mengembangkan aplikasi media pembelajaran untuk membantu peserta uji kompetensi dalam mempelajari materi yang akan diujikan. Rumusan masalah pada penelitian ini adalah: (1) Bagaimana mengembangkan Media Pembelajaran Berbasis Web Pada Uji Kompetensi Skema Sertifikasi Teknisi Muda Jaringan Komputer. (2) Bagaimana kualitas Media Pembelajaran Berbasis Web Pada Uji Kompetensi Skema Sertifikasi Teknisi Muda Jaringan Komputer. (3) Bagaimana respons peserta terhadap Media Pembelajaran Berbasis Web Pada Uji Kompetensi Skema Sertifikasi Teknisi Muda Jaringan Komputer. Metode penelitian yang digunakan merupakan metode Watefall. Sasaran penelitian pada penelitian ini merupakan 20 mahasiswa yang sedang atau sudah mengikuti mata kuliah jaringan komputer. Hasil penelitian menunjukkan bahwa: (1) Media Pembelajaran yang dikembangkan medapat presentase 86,76% dari penilaian dari validator. Presentase tersebut termasuk dalam kategori sangat layak dengan rentang presentase 81%-100%. Berdasarkan pada hasil penelitian, dapat disimpulkan bahwa aplikasi media pembelajaran ini sangat setuju di uji coba dari validator media. Kata Kunci: Aplikasi, Media Pembelajaran, Website.